A study of somatic cell and their relation to some milk traits and udder measurements in Black and Meriz goats - Alkass, Jalal E.; Merkhan, Kawa Y. (Sulaimani Journal for Pure and Applied Sciences, 2014)
A total of 246 observation of test day milk yield (TDMY), fat percent and somatic cell count (SCC) of 25 lactating does (2-6 years old) from each of Black and Meriz goat were used in this study. Milk yield was recorded at monthly intervals, commencing from the 30th day after kidding till the does were dried off. Also, the external udder measurements of does were performed. Results revealed that a non-significant negative correlations were found between SCC and TDMY in both Meriz and Black goats except that at 3rd collection in Black goat was significant (r=-0.421, P<0.05). Fat content was positively correlated with SCC (P>0.05) in both breeds. In Meriz goat, SCC was negatively correlated with udder circumference (r=-0.550, P<0.01) and positively correlated with each of teat diameter (r=0.559, P<0.01) and teat length (r=0.665, P<0.01). All the correlation coefficients between SCC and udder measurements in Black goat were not significant.
Keywords: Somatic cell Count Test day milk yield Udder measurements Does